Acid Gas Removal in Geothermal Power Plant in Iceland. (January 2016) - Berstad, David; Nord, Lars O.
Abstract: A large part of the energy covering the electricity and heating demands in Iceland is generated in geothermal power plants. The Hellisheiði power plant, designed for 300 MWe and 133 MWth, is located in close proximity to Reykjavik. The concept of the plant is to co-generate power for energy-intensive industry and hot water for district heating. The steam at Hellisheiði is not pure H2 O, but also contains H2 S, CO2, H2, N2, and CH4 . These gases have, for the most part, been emitted to the atmosphere after separation from the steam. New, emerging environmental regulations in Iceland will limit the emission of H2 S. Additionally, the long-term goal is to decrease CO2 emissions. Therefore, separation of CO2 and H2 S from the non-condensable gases in the steam will be necessary, followed by some measure to store these. In this work, four different acid gas capture systems were selected and subsequently modelled and simulated: water absorption, amine absorption with MDEA, amine/low temperature hybrid concept, and stand-alone low-temperature separation. For co-removal of H2 S and CO2, low-temperature separation seems to be an attractive alternative to the conventional water absorption process due to the low power penalty.